1995
DOI: 10.1096/fasebj.9.5.7896015
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant glycosylasparaginase and in vitro correction of aspartylglycosaminuria

Abstract: Aspartylglycosaminuria (AGU) is the most common disorder of glycoprotein degradation. AGU patients are deficient in glycosylasparaginase (GA), which results in accumulation of aspartylglucosamine in body fluids and tissues. Human glycosylasparaginase was stably overexpressed in NIH-3T3 mouse fibroblasts, in which the unusual posttranslational processing and maturation of the enzyme occurred in a high degree. The recombinant enzyme was isolated as two isoforms, which were both phosphorylated, and actively trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The above mentioned results, along with our earlier results that enzyme replacement therapy with glycosylasparaginase effectively removes the lysosomal storage of GlcNAc-Asn from glycosylasparaginase-deficient cell lines 4 and mice, 5 led us to consider GA as a potential cytotoxic enzyme against L-asparagine-dependent leukemia cells. We supplemented the culture medium of two different leukemic cell lines, human B-cell precursor leukemia SUP-B15 cells and human T-lineage leukemia CCRF-CEM cells, either with GA, dephosphorylated (c) The L-asparaginase activity in the EBV-transformed lymphoblasts after addition of GA 40 U/l ('), ErAII 40 U/l (J), ErAII 150 U/l (&), ErAII 1500 U/l (K) into the culture medium, or in the absence of enzymes (n).…”
Section: Depletion Of L-asparagine Supply and Apoptosis Of Leukemia Cmentioning
confidence: 80%
See 4 more Smart Citations
“…The above mentioned results, along with our earlier results that enzyme replacement therapy with glycosylasparaginase effectively removes the lysosomal storage of GlcNAc-Asn from glycosylasparaginase-deficient cell lines 4 and mice, 5 led us to consider GA as a potential cytotoxic enzyme against L-asparagine-dependent leukemia cells. We supplemented the culture medium of two different leukemic cell lines, human B-cell precursor leukemia SUP-B15 cells and human T-lineage leukemia CCRF-CEM cells, either with GA, dephosphorylated (c) The L-asparaginase activity in the EBV-transformed lymphoblasts after addition of GA 40 U/l ('), ErAII 40 U/l (J), ErAII 150 U/l (&), ErAII 1500 U/l (K) into the culture medium, or in the absence of enzymes (n).…”
Section: Depletion Of L-asparagine Supply and Apoptosis Of Leukemia Cmentioning
confidence: 80%
“…Earlier studies have shown that GA is actively transported into glycosylasparaginase-deficient lymphoblasts, in which it locates mostly in the cytoplasm and lysosomes. 4 The location of ErAII in the lymphoblasts was not studied in this work. In theory, the observed L-asparaginase activity in lysed lymphoblasts could result from ErAII attached to the cell membrane or from enzyme that has entered the cells, or both.…”
Section: Referencesmentioning
confidence: 98%
See 3 more Smart Citations